SPEED CONTROL SYSTEM OF BLDC MOTOR WITH DIGITAL PI ANTI-WINDUP CONTROLLERS - Ariefka Septian Putra, Febi
This study contains about control of 2 BLDC motors which have a different characteristic as an actuactor system of an autonomous mobile. A characteristic difference is a what causing of both motors for having a different settling time for reaching their steady state. The purpose of this study is for making both motors to have samely speed on getting their system response so that the mobile can be easily controlled on straight or turning mode. The method that used is PI Anti-Windup control system. The design is made by system modelling on SysId MATLAB by viewing the system response when given a PWM input which the value is on range of operation point with linear approach from motor speed. After setting a straight line on a response graph, then BLDC will be given a random set of setpoint that comes from a staright line for obtain the speed data. A measured speed on RPM is used for determining Kp dan Ki values analytically with ideal state without saturation. After Kp and Ki values obtained, it will be simulated using PI Anti-Windup control system. On the implementation, only a positive control signals are used for making motor to rotate without having any braking effect. From simulation and implementation, its clear that PI Anti-Windup control system is capable to manage 2 BLDC motors that have a different characteristic for not only having a same response speed to reach a steady state, but also having an overshoot and steady state error’s value towards 0%.